Are dual and single exposures differently associated with clinical levels of trauma symptoms? Examining physical abuse and witnessing intimate partner violence among young children. Issue 2 (5th September 2019) - Showalter, Kathryn; Yoon, Susan; Maguire‐Jack, Kathryn; Wolf, Kathryn G.; Letson, Megan
Abstract: A significant portion of children living in the United States have experienced trauma. Informed by the developmental traumatology model, we explored the effects of physical abuse and witnessing intimate partner violence (IPV) on childhood trauma symptoms. This study utilizes a convenience sample of 580 high‐risk children between 3 and 12 years who received services from one‐child advocacy centre during a 12‐month period. We performed a series of binary logistic regression analyses to examine if physical abuse, exposure to IPV, and dual exposure (i.e., both physical abuse and IPV) are distinctly associated with six trauma symptoms, including anxiety, depression, posttraumatic stress (PTS), dissociation, anger, and sexual concerns. The results indicated that dual exposure was predictive of all trauma symptoms, except for dissociation. Additionally, physical abuse was associated with PTS, anger, and sexual concerns, whereas exposure to IPV was associated with depression, PTS, and sexual concerns. Research and implications for practitioners working with young children are discussed.